Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1469-8749.2008.03173.x
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the nerve growth factor beta gene in a 1p13 deleted female child with an insensitivity to pain

Abstract: Pain insensitivity is mediated at the genetic level by the disruption of specific genes associated with neuronal development. Mammalian in vivo and in vitro studies have shown the nerve growth factor (NGF) gene to play an integral role in nerve maintenance and function. Pain insensitivity in humans can be attributed to hereditary sensory and autonomic neuropathies (HSAN) of which there are five classes (HSAN I – HSAN V). The human nerve growth factor beta gene (NGFB) located on chromosome 1p13.2 has been found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A study performed on a large cohort of HSAN patients from UK revealed that two out of 140 subjects had a phenotype that could be ascribed to HSAN V, and were carriers of a duplication or mutation (p.Ser187Asn) in the NGFB gene, the pathogenicity of which is still to be demonstrated (Davidson et al ., ). The attribution to HSAN V to a case described in the UK, in which a deletion within the chromosome 1p13 determined an haploinsufficiency of the NGFB gene (Fitzgibbon et al ., ), is also controversial.…”
Section: Genetics and Epidemiology Of Hsan Vmentioning
confidence: 99%
“…A study performed on a large cohort of HSAN patients from UK revealed that two out of 140 subjects had a phenotype that could be ascribed to HSAN V, and were carriers of a duplication or mutation (p.Ser187Asn) in the NGFB gene, the pathogenicity of which is still to be demonstrated (Davidson et al ., ). The attribution to HSAN V to a case described in the UK, in which a deletion within the chromosome 1p13 determined an haploinsufficiency of the NGFB gene (Fitzgibbon et al ., ), is also controversial.…”
Section: Genetics and Epidemiology Of Hsan Vmentioning
confidence: 99%
“…Animal studies demonstrated that BDNF regulates the mesolimbic dopamine pathway and is involved in the response to aversive social experiences 17. There are only a few studies of the effect of NGFB genetic variability in humans, mostly related to insensitivity to pain 182021.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated chromosome 1p13.2 microdeletions are not common; we could find only three individuals reported in the literature (Mattia et al ., 1992; Bisgaard et al ., 2007; Fitzgibbon et al ., 2009). Additionally, six patients with isolated deletions partially overlapping the one of our patient had been reported previously in DECIPHER database.…”
Section: Resultsmentioning
confidence: 99%
“…We concluded that the clinical characteristics of the patient could be attributed to the 1p13.2 haploinsufficiency. Additionally, we compared his clinical characteristics with the phenotype of six patients with similar deletions overlapping the one of our patient reported previously in DECIPHER database and three individuals reported in the literature (Mattia et al ., 1992; Bisgaard et al ., 2007; Fitzgibbon et al ., 2009). On these bases we propose that haploinsufficiency of NRAS gene (OMIM *164790) may be important in determining the clinical phenotype of this microdeletion.…”
Section: Introductionmentioning
confidence: 99%